The impact of face‐to‐face mental health consumer‐led teaching on occupational therapy student empathy levels: Two group comparison design. (10th August 2022) - Logan, Alexandra; Yule, Elisa; Hughes, Julie; Peters, Dave; Hadley, Melanie; Betts, Brodie; Jones, Lee; Froude, Elspeth
Abstract: Introduction: Australian and New Zealand accreditation standards for occupational therapy courses mandate consumer involvement in the design, delivery, and evaluation of courses. Consumer involvement in medical, dental, and nursing education has been evidenced as a factor for increasing student empathy. To date, there has been no known research on the impact of mental health consumer involvement on occupational therapy students' empathy. The aim of this study was to investigate if occupational therapy students who receive teaching from a mental health consumer demonstrate higher levels of empathy compared with students who receive teaching delivered by occupational therapy academics. Methods: Pre–post, quasi experimental, two group comparison design was used to measure second‐year student empathy pre and post a consumer‐led teaching tutorial. Students ( N  = 217) were randomised into two groups across three university campuses: 'teaching as usual group' (control) or 'consumer‐led' group (experimental group). The Jefferson Scale of Empathy was used to measure student empathy. Results: N  = 138 matched scales were returned. Little difference in empathy scales was detected between groups. The 'consumer‐led' group increased for the empathy scale by 3.4(95% CI: 0.7, 6.1, p  = 0.014) but was not statistically significant compared to 1.3(95% CI: −1.0, 3.5, p  = 0.267) for the control group. Both groups scored highly on empathy. Conclusion: This study found that occupational therapy students had pre‐existing high levels of empathy. The challenge for future research is to identify appropriate ways to measure the impact of mental health consumer involvement on occupational therapy curriculum and students.